Factors influencing aerosol and precipitation ion chemistry in urban background of Moscow megacity. (1st February 2023) - Zappi, Alessandro; Popovicheva, Olga; Tositti, Laura; Chichaeva, Marina; Eremina, Irina; Kasper-Giebl, Anne; Tsai, Ying I.; Vlasov, Dmitry; Kasimov, Nikolay
Abstract: In-depth study of aerosol and precipitation ion chemistry was carried out in order to cover an existing data gap in the seasonal-dependent ionic data in Moscow urban background atmosphere. Literature about atmospheric pollution in this megacity is, indeed, still poor, despite its peculiar climatological characteristics that make it a very interesting site for atmospheric research. Particulate matter (PM) and precipitation were collected at Moscow urban background during spring of 2018, summer, and autumn of 2019. Aerosol inorganic ions are characterized for the whole period, carboxylic acids and sugars for summer. Inorganic ions constitute a major PM10 fraction of 27% in autumn, it drops down to 16.5% in summer. Dominance of secondary inorganic aerosol (SIA) over all the other inorganic ion species is determined. Na + and Ca 2+ shows the largest variability between seasons, with maximum in summer and spring, respectively. Excess of anions in autumn is indicated by ion balance while adding carbonates, spring and summer aerosol is found electroneutral. Chloride depletion phenomenon follows the snow melt and remobilization of salt applied to roads for deicing, demonstrating the biggest impact in summer. Degree of neutralization of ammonia as sulfate and nitrate is found by the correlation between the concentration of NH4 + and calculated from SO4 2− and NO3 − . Inorganic fraction in PM10 is higher (16.5%) than total carboxylic acids (3.5%), and total sugars and anhydrosugars (0.8%). Concentration polar plots show ion variation jointly with wind speed and wind direction and the source origin. Highest SIA concentrations relate a cluster of the prevalent air mass transportation and indicate the source in the northwestern direction in spring and summer. K + acts as a marker of fires in spring and summer as well as of the domestic biomass burning in the region around a megacity in autumn. Source apportionment of inorganic ion and BC by Varimax analysis reveals major sources namely SIA, soil resuspension, biomass burning, deicing salt, and fossil fuel combustion. In summer, organic ions, anhydrosugars, and sugars shows additional impact of photochemistry and biological activities. Rainfall is heavier in summer than in autumn, with pH of acid rain during spring and summer. The highest concentrations for almost all ions were observed in spring, except HCO3 − . Precipitation composition is described with aerosol wet removal by seasonal variability of SIA scavenging factors, decreasing in summer and increasing in autumn and spring. Highlights: First aerosol ion PM10 speciation in Moscow megacity. Aerosol is acid in autumn and neutralized in spring and summer. Ion sources are secondary inorganic, soil resuspension, deicing, and biomass burning. Higher rain acidity in summer and spring.